2022
DOI: 10.3390/children9091306
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Intervention Programs in Minors Belonging to Disadvantaged Contexts in Spain: A Systematic Review

Abstract: Research studies show a strong influence of socioeconomic status (SES) on human development, and how the exposure to risk contexts in the earliest stages translates into dangers in the cognitive development of children and adolescents. To alleviate these consequences and favour development, different cognitive training programs have contributed to this field by identifying the criteria of efficacy. This systematic review identifies and synthesizes the evidence of cognitive intervention studies implemented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The specific objective was the development of a comprehensive neuropsychological stimulation program in which the following cognitive and emotional functions were intervened: attention, language, executive functions, social cognition, and emotional competence. This comprehensive intervention responds to the needs detected in recent previous experiences, and we hypothesise that the strengthening of cognitive abilities and emotional competence will improve their overall health and well-being, as of previous studies have shown [16][17][18].…”
Section: 2objectives and Hypothesismentioning
confidence: 75%
See 3 more Smart Citations
“…The specific objective was the development of a comprehensive neuropsychological stimulation program in which the following cognitive and emotional functions were intervened: attention, language, executive functions, social cognition, and emotional competence. This comprehensive intervention responds to the needs detected in recent previous experiences, and we hypothesise that the strengthening of cognitive abilities and emotional competence will improve their overall health and well-being, as of previous studies have shown [16][17][18].…”
Section: 2objectives and Hypothesismentioning
confidence: 75%
“…For this reason, actions to strengthen emotional intelligence are included. Scientific evidence shows that, in addition to improving concentration and academic performance, this type of intervention promotes the prevention of the appearance of violent, addictive behaviours, and other behaviours associated with impulsiveness and difficulty in long-term planning, thus contributing to personal and collective empowerment of these children [18,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), with a wide range of activities, games, and other media, so patients can improve cognitive skills that are not fully acquired/developed (due to neurodevelopmental disorders) or have declined (due to acquired brain damage or degenerative illnesses). In addition, research exists demonstrating the efficacy of neuropsychological interventions focused on specific cognitive domains in non-clinical child populations belonging to socioeconomically vulnerable contexts [ 25 , 26 , 27 ]. The results suggest that protocols employing different agents and materials in cognitive intervention, with early intervention and a large number of sessions, are the most effective.…”
Section: Introductionmentioning
confidence: 99%